The Application For A Tourist Service Permit Is Reviewed From The State Administrative Law Based On Law Number 32 Of 2024 Concerning The Conservation Of Biological Natural Resources And Their Ecosystems (Case Study Of Situgunung Motorcycle Taxi Tour Services) - Putra, Bangkit Tri Bakti; Haidan Angga Kusumah; Asti Sri Mulyanti (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2025)
This study aims to analyze the problems in the application for tourism service permits in the Situgunung conservation area from the perspective of the State Administration Law (HAN), with reference to Law Number 32 of 2024 concerning the Conservation of Biological Natural Resources and Their Ecosystems. This study focuses on the practice of implementing motorcycle taxi services as part of the use of environmental services which should be subject to the provisions of valid licensing from the government and/or local governments as stipulated in Article 34 paragraph (4) of the Law. However, in its implementation, it was found that the activities of motorcycle taxi services in Situgunung ran without a legal licensing basis, and escaped administrative supervision that should be carried out by the relevant authorities. This problem shows that there is a discrepancy between legal norms and administrative practices, weak enforcement of the principle of legality, and the lack of effectiveness of bureaucratic supervision in the implementation of the risk-based licensing system through OSS. Using a normative juridical approach and a field study, this study seeks to provide a critical evaluation of the existing permit application mechanism, as well as formulate the urgency of improving the licensing system to be in line with the principles of good governance, legal certainty, and administrative order in the sustainable management of conservation areas.